MANAJEMEN KINERJA GURU SMP DI SEKOLAH PSKD MANDIRI - Tri Maelina (Jurnal Manajemen Pendidikan, 2016)
The objective of this research is to gain a deep understanding of performance management of junior High School teachers in PSKD Mandiri School. This research is a case study method. The validity of qualitative data obtained through the extension of time doing research and triangulation of data collection techniques and data sources in the field. The result shows: 1) teacher’s performance evaluation has two type; formally in each semester and in formally. Teacher was evaluated by principal, training and mentoring staff, students, colleagues and teacher itself. 2) Training was held in the first of the years, in the middle of the year and weekly. The purpose is to develop teacher performance and professionalism. Training is presented by training and mentoring staff, teachers, other department such as finance or human resources, and organizations.